1990
DOI: 10.1002/pd.1970101005
|View full text |Cite
|
Sign up to set email alerts
|

First and early second‐trimester diagnosis of fetal urinary tract anomalies using transvaginal sonography

Abstract: Urinary tract anomalies are common. Prenatal diagnosis is important and enables either special obstetric management or termination of pregnancy and probably in the future, intrauterine intervention. Transvaginal sonography (TVS) allows visualization of the normal and anomalous fetal urinary tract at an early stage. One thousand nine hundred and forty women were examined via TVS at an early stage of pregnancy between 10 and 16 weeks from the last menstrual period (LMP) and 35 anomalies (1.8 per cent) were clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 13 publications
0
36
0
4
Order By: Relevance
“…[5][6][7] This was true for 115 (47%) of the 245 cases registered at the National Multicystic Kidney Registry. 8 Indeed, the most common reason for referral of the patients in the present study was a prenatal diagnosis of a renal abnormality.…”
Section: Discussionmentioning
confidence: 96%
“…[5][6][7] This was true for 115 (47%) of the 245 cases registered at the National Multicystic Kidney Registry. 8 Indeed, the most common reason for referral of the patients in the present study was a prenatal diagnosis of a renal abnormality.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed in one reported case in which the bladder measured 30 mm, vesicocentesis was deferred until 22 weeks by which time bilateral renal damage had already occurred 9 . In another three untreated cases with bladder diameters of 30 mm, intrauterine death or progressive complications of obstructive uropathy occurred 5,10,11 . It has been shown that the survival rate following second-trimester vesicoamniotic shunt placement for obstructive uropathy ranges from 41 to 70% depending on etiology 12 with 36% of cases developing renal failure necessitating transplantation 13 .…”
Section: Vesicocentesis At 10-14 Weeks Carroll Et Almentioning
confidence: 99%
“…Depending on the fluid volume, fetal karyotype may be determined either from the bladder aspirate or from simultaneous amniocentesis. In cases of bladder outlet obstruction at 10-14 weeks there should be sufficient amniotic fluid volume for karyotyping because the quantitative contribution of fetal urine to the amniotic fluid volume is minimal before 16 weeks' gestation 10 . However, because of the potential benefits of early vesicocentesis, we think that if intervention is to be tried it should not be deferred until karyotype results are available.…”
Section: Vesicocentesis At 10-14 Weeks Carroll Et Almentioning
confidence: 99%
“…Evaluation of fetal kidney biometry must be included in the guidelines for an early transvaginal scan and, since the first sign of malformation could be an enlarged kidney [2], measurement of the kidney parameters is recommended in all cases.…”
Section: Introductionmentioning
confidence: 99%